2012
DOI: 10.1101/cshperspect.a007021
|View full text |Cite
|
Sign up to set email alerts
|

Treg Cells, Life History, and Diversity

Abstract: Regulatory T cells expressing the FoxP3 transcription factor have a profound and nonredundant role in several aspects of immunological tolerance. We will review here the specification of this lineage, its population dynamics, and the diversity of subphenotypes that correlate with their diverse roles in controlling inflammation in a variety of settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
105
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 159 publications
2
105
0
2
Order By: Relevance
“…However, it is now clear that in humans, Tregs are in fact a heterogeneous mixture of cellular subphenotypes reflecting different states of maturation, differentiation, and activation (reviewed in Refs. [14][15][16]. Several studies have identified cellular markers differentially expressed within the FOXP3 + T cell (and CD25 hi CD127 lo ) population that delineate cells with distinct developmental states, capacities, and methods of suppression, homing properties as well as targets of suppression.…”
mentioning
confidence: 99%
“…However, it is now clear that in humans, Tregs are in fact a heterogeneous mixture of cellular subphenotypes reflecting different states of maturation, differentiation, and activation (reviewed in Refs. [14][15][16]. Several studies have identified cellular markers differentially expressed within the FOXP3 + T cell (and CD25 hi CD127 lo ) population that delineate cells with distinct developmental states, capacities, and methods of suppression, homing properties as well as targets of suppression.…”
mentioning
confidence: 99%
“…immunoregulation | suppression C D4 + FOXP3 + regulatory T (Treg) cells are important mediators of immune tolerance, prevent overwhelming immune responses, and regulate extraimmunological functions (1)(2)(3). Their absence leads to lethal lymphoproliferation and multiorgan autoimmunity in scurfy mice and in patients with immunodysregulation polyendocrinopathy enteropathy X-linked syndrome.…”
mentioning
confidence: 99%
“…The Tregs that develop in the thymus are known as naturally occurring Treg cells and the adaptive Tregs that are induced by various stimulations such as an antigen (Benoist and Mathis, 2012;French and Kinter, 2012;Robertson and Hasenkrug, 2006;. Naturally occurring CD4+CD25+ regulatory T cells have been shown to constitute 5-15% of peripheral CD4+ T in both mice and humans (Sakaguchi, 2003).…”
Section: Regulatory T Cellsmentioning
confidence: 99%